Studies on Effect of Intensity and Interval of Defoliation on Forage Production of Dichanthium Annulatumn (Forsk) Stapf - Roy, R Deb; Das, R B; Bhati, G N (Annals of Arid Zone, 2016)
Investigations on the effect of height and frequency of defoliation on performance of Dichanthium annulatum (Forsk.) Stapf. at Research Farm, Pali of the Central Arid Zone Research Institute, Jodhpur were carried out from 1962 to 1963. The results obtained have been found to be significant for one year out of the two 1962-63 (season) in case of interval and intensity of the defoliation. It has also been observed that dry matter production increases with increasing interval of clipping. Highest production was obtained under 30 days intervals followed by 20 days and 10 days. Therefore, the recommendations are for cutting or grazing of this grass at the interval of 30 days and the level of utilisation may be upto the extent leaving a stubble height of IS cm from the ground.